Studying the Pollution of Tigris River Sediments Between Al-Qayara-Balad - Zarraq, Ghazi (Iraqi Journal of Science, 2024)
This study including recognition ofdifferent minerals in Tigris River sedimentswithin grain size (ø>.:) andclay minerals in (5.0ø) grain size, The main mineralsthat identified are Quartz, Calcite and Feldspare, The clay minerals are illite,chlorite, kaolinite, palygorskite and montmorilonite, The heavy minerals are biotite,epidot, hornblend, zircon, rutile and muscovite. The source of these sediments areigneousand metamorphic rocks which are found in Northern Iraq within Tigriscatchments area, or derived from Fat7ha and Injana formations outcropedin part ofthe area, or may be formed by digenesis processes.The most common trace elements that have been identified which have local effectare Cd, Zn, Ni, & Cu of higher concentration more than the natural abundant, thereare a local environmental pollutant in the sediments, may be due to the waste waterand heavy industrial remains along the river valley, from the fertilizing industrial processing and heavy remains of oil from Baiji refinery plant. The othertrace elements are Pb, Fe, Cr, Co, Mn, Se& Ag. The major elements Ca, Mg, K &Na, all of them are of normal concentration in Tigris River sediments. materials,